MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI SD NEGERI 01 PRATAMA MANDIRA KECAMATAN SUNGAI MENANG TAHUN PELAJARAN 2021/0222 - NURLENDA; Erjati Abbas; Etika Pujianti (UNISAN JURNAL, 2022)
There are two main problems faced by religious people in general. On the one hand, we are faced with economic, political, legal and other problems as a result of the national crisis in this field. On the other hand, we are also faced with problems between religious communities and even between internal adherents of the religion itself which has not shown a close, compact and harmonious relationship. If these two problems cannot be solved immediately, it is likely that the national crisis will get worse and spread to various sectors of life. In order to anticipate these various problems, the learning of Islamic religious education in schools must show its contribution. Because Islamic Religious Education in schools still often gets criticism from experts, it is necessary to improve the quality of learning. To improve the quality of Islamic Religious Education learning in schools, there are many factors that influence it, one of which is the factor of educational facilities and infrastructure. Because without adequate facilities and infrastructure, learning will not run effectively and efficiently. Based on this, the authors are interested in taking the title: "The Relationship of Educational Facilities and Infrastructure Management with Improving the Quality of Islamic Religious Education Learning at SD Negeri 01 Pratama Mandira. From the above background, the problems that want to be raised are what are the facilities and infrastructure needed to improve the quality of learning Islamic Religious Education in SD Negeri 01 Pratama Mandira, how is the process of managing educational facilities and infrastructure in improving the quality of learning Islamic Religious Education in SD Negeri 01 Pratama Mandira, and how are the results of improving the quality of Islamic Religious Education learning at SD Negeri 01 Pratama Mandira, Sungai Menang District, Ogan Komering Ilir Regency through the management of educational facilities and infrastructure. The objectives to be achieved in Islamic Religious Education in this problem are to find out the facilities and infrastructure needed to improve the quality of Islamic religious education learning at SD Negeri 01 Pratama Mandira, to know the process of managing facilities and infrastructure. Educational infrastructure in improving the quality of Islamic Religious Education learning at SD Negeri 01 Pratama Mandira, and to find out the results of improving the quality of learning Islamic Religious Education at SD Negeri 01 Pratama Mandira, Sungai Menang District, Ogan Komering Ilir Regency through the management of educational facilities and infrastructure.This research was conducted using descriptive qualitative research, because with the aim to describe or describe the phenomena that are in the research location. And so that the research results can be arranged systematically, the researchers’ steps in analyzing the data are; First, by reducing data, namely summarizing, choosing the main things and focusing on the things that are important. Keywords: Management and Infrastructure